2006
DOI: 10.1191/0265659006ct304oa
|View full text |Cite
|
Sign up to set email alerts
|

Teacher judgements of the language skills of children in the early years of schooling

Abstract: Language impairments are often associated with problems in educational attainments and in acquiring literacy, but speech therapy services to school-aged children are not universally available. If teachers are able to reliably identify those children whose language skills place them at risk, then the specialist services offered by speech and language therapists (pathologists) may be used in more productive ways. The current study compared teacher judgements with formal testing of general language ability and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
3
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 18 publications
0
25
3
9
Order By: Relevance
“…Na Austrália, os professores do pré-primário e da primeira série foram capazes de identificar crianças de risco para dificuldades de linguagem (23) . No Brasil, uma pesquisa mostra a discrepância entre a avaliação realizada no estudo com a da professora da rede pública (24) .…”
Section: Discussionunclassified
“…Na Austrália, os professores do pré-primário e da primeira série foram capazes de identificar crianças de risco para dificuldades de linguagem (23) . No Brasil, uma pesquisa mostra a discrepância entre a avaliação realizada no estudo com a da professora da rede pública (24) .…”
Section: Discussionunclassified
“…Teachers' judgments have been compared with formal test outcomes of general language ability and phonological awareness for pre-primary and kindergarten children (Williams 2006). Teachers' judgments were more accurate for pre-primary children than for the complete group of children (kindergarten and pre-primary) or for the group of kindergarten children alone.…”
Section: Introductionmentioning
confidence: 99%
“…Current research suggests that teachers' ratings of children's performance are associated with direct behavioral assessments of children's skills, but their ratings tend to be more accurate for younger children (Williams 2006), less accurate for children who are at-risk for literacy problems (Cabell et al 2009), and teachers' ratings of domain-specific skills (print knowledge, oral language) are associated with direct assessments of these skills (Farrington and Lonigan 2010). Researchers have previously used a variety of measures to gather teachers' ratings of children's language and literacy skills.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature has found only a small number of prior studies which have reported data concerning the rate of teacher identification of speech and language impairment amongst particular student populations (Diehl & Stinnett, 1959;Illerbrun, Haines, & Greenough, 1985;James & Cooper, 1966;McKinnon, McLeod, & Reilly, 2007;Okalidou & Kampanaros, 2000;Sanger, Aspedon, Hux, & Chapman, 1995;Whitworth, Davies, Stokes, & Blain, 1993;Williams, 2006). An even fewer number of studies have examined the effectiveness of specific screening tools in supporting teachers to identify students with speech and/or language impairment (Diehl & Stinnett, 1959;James & Cooper, 1966;Illerbrun et al, 1985;Whitworth et al, 1993;Williams, 2006), with the majority of these studies failing to report adequate data on both the numbers of students correctly identified (true positive), and overlooked (false negative).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to language impairment, a recent study by Williams (2006) examined the ability of teaching professionals to identify students enrolled in kindergarten, preparatory and grade 1 with such difficulties. A total of 29 teachers across five schools in Western Australia initially received a full day of inservicing to build their knowledge of language impairment, methods to identify children with such problems and classroom strategies to facilitate language development.…”
Section: Introductionmentioning
confidence: 99%